SYSTEM OF POLITICAL ORGANIZATION OF THE WORLD: ‘PERFECT STORM’ - M. M. Lebedeva (Vestnik MGIMO-Universiteta)
The paper proposes to examine the modern political organization of the world as a global system consisting of three levels: Westphalian systems, system of international (interstate) relations, and political systems of states.It shows that all three levels are currently subject to a deep transformation that produces the effect of a 'perfect storm'. The Middle East due to a number of reasons is the most 'weak link', i.e. the link where these processes are manifested with the greatest force. Such situation, when all three levels are in a deep changing, is unique. The world has not previously faced with it. The article discusses possible scenarios for the further development of the system of political organization of the world.